دلالة الصفة المشبهة في سورة الإسراء -دراسة صرفية نحوية - عمراني، اسماء; خياري، نور الهدى (University of Eloued جامعة الوادي, 2025)
الملخص: هدفت هذه الدراسة إلى الكشف عن دلالة الصفة المشبهة في سورة الإسراء من خلال مقاربة صرفية ونحوية. انطلقت الدراسة من إشكالية تكمن في تبيان الوظيفة الدلالية التي تؤديها الصفة المشبهة في سياق آيات السورة الكريمة، وكيف يسهم بناؤها الصرفي وموقعها النحوي في تعميق هذه الدلالة وإبراز جوانب من الإعجاز اللغوي في النص القرآني. اعتمدت الدراسة المنهج الوصفي التحليلي، إذ تم استقراء جميع الألفاظ التي وردت بصيغة الصفة المشبهة في سورة الإسراء، ثم تحليلها صرفياً لتحديد أوزانها المختلفة وبيان مصادر اشتقاقها، ونحوياً لتوضيح مواقعها الإعرابية ووظائفها داخل التراكيب والجمل. بعد ذلك، تم تحليل الدلالات المعنوية لهذه الصفات في سياقاتها القرآنية، مع التركيز على دلالة الثبوت والدوام التي تميز الصفة المشبهة عن غيرها من المشتقات العاملة. وقد توصلت الدراسة إلى مجموعة من النتائج أهمها: أن سورة الإسراء تضمنت عدداً من الصفات المشبهة على أوزان متنوعة، وأن هذه الصفات قد وردت في مواقع إعرابية مختلفة (نعت، خبر، حال، إلخ)، وأن بنائها الصرفي ووظيفتها النحوية قد تضافرا ليكسِبا المعنى في الآيات دلالة الثبوت والرسوخ، مما يعزز المعاني القرآنية المتعلقة بصفات الله تعالى، أو صفات العباد، أو الحقائق الكونية والتشريعية التي تتسم بالدوام والثبات. وتكمن أهمية الصفة المشبهة في السورة في قدرتها على تصوير المعاني وتثبيتها في ذهن المتلقي، مما يخدم المقاصد الكلية للسورة. Abstract: This study aimed to uncover the meaning of the adjective in Surat Al-Isra' through a morphological and syntactic approach. The study began with a problem that lies in clarifying the semantic function performed by the adjective in the context of the verses of the Holy Surah, and how its morphological structure and grammatical position contribute to deepening this meaning and highlighting aspects of the linguistic miracle of the Quranic text. The study adopted a descriptive and analytical approach, where all words that appear in the form of the adjective in Surat Al-Isra' were inductively examined, then analyzed morphologically to determine their different weights and identify their derivational sources. Grammatically, the analysis clarified their grammatical positions and functions within structures and sentences. The semantic connotations of these adjectives were then analyzed in their Quranic contexts, with a focus on the connotations of permanence and permanence that distinguish the adjective from other functional derivatives. The study reached a set of results, the most important of which are: Surat Al-Isra' includes a number of similitudes in various forms, and that these similitudes occur in different syntactic positions (adjective, predicate, state, etc.), and that their morphological structure and grammatical function combine to give the meaning of the verses a sense of permanence and stability, reinforcing the Qur'anic meanings related to the attributes of God Almighty, the attributes of His servants, or cosmic and legislative truths characterized by permanence and stability. The importance of the similitude in the surah lies in its ability to portray meanings and fix them in the mind of the recipient, thus serving the overall objectives of the surah.
مذكرة ماستر.لسانيات عامة.2025
Keywords: الصفة المشبهة، سورة الإسراء، دراسة صرفية، دراسة نحوية، دلالة، القرآن الكريم، ثبوت; similitude; Surat Al-Isra'; morphological study; grammatical study; semantics; the Holy Qur'an; permanence